TI_GERICHTE 14.2011.155 vom 21. Oktober 2011 , Reclamo contro la dichiarazione di fallimento. Nova in senso proprio. Solvibilitâ - TI Tribunale d'appello (2011)
Reclamo contro la dichiarazione di fallimento. Nova in senso proprio. Solvibilitâ